Pengembangan Karakter Melalui Implementasi Literasi Baca Quran di SMP Negeri 1 Sungai Pua - Linda Puspitasari; Bagus Bara Sofani; Sellina Diah Rifani (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2024)
This research discusses student character development through the implementation of a Quran reading literacy program at SMP Negeri 1 Sungai Pua. This program aims to improve students' understanding and skills in reading the Koran, as well as to form strong characters based on Islamic values. The research method used was an experiment with a pretest-posttest control group design, where students were divided into an experimental group that took part in the Quran reading literacy program and a control group that did not take part in the program. Data was collected through Quran reading comprehension tests and character scales. Data analysis was carried out using descriptive and inferential statistical techniques. The research results show that the implementation of the Quran reading literacy program significantly increases students' understanding of Quran reading and shapes their character in accordance with Islamic values.